Detailed Parametric Investigation and Optimization of a Composite Wing with High Aspect Ratio. (11th July 2019) - Meng, Yu-shan; Yan, Li; Huang, Wei; Zhang, Tian-tian
Abstract : The large deformation problem of the wing with high aspect ratio cannot be avoided due to the large bending moment and poor torsional stiffness. The wing design follows the following procedure; firstly, the design indexes of high aspect ratio wing are preliminarily formulated referring to some parameters of the Predator UAV. Then, the aerodynamic analysis of the wing is performed, and the stress cloud diagram is obtained. Next, the finite element model of the wing is designed, and the static analysis is conducted in the ANSYS ACP module, and the unreasonable component size is changed. An appropriate thickness which is 12 mm is selected as the final thickness of the wing. Then, the analysis of laying methods of skin structure is conducted. Finally, the composite structure is proved to reduce the maximum deformation and maximum stress effectively compared with the metal wing.